Peningkatan Kemampuan Mengklasifikasikan Warna Dengan Media Kancing Warna Dalam Kegiatan Meronce Anak Usia 4-5 Tahun - Endah Jubaedah; Aas Sa'adah (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2026)
The ability to classify colors is an important aspect in the cognitive development of early childhood that needs to be developed, because it influences the subsequent learning process. This research is motivated by the low ability to classify colors in children at Aisyiyah Bustanul Athfal II Kindergarten (Aisyiyah BA II Kindergarten), which is caused by the lack of variety in learning methods and the limited learning media used. This study aims to determine the improvement in the ability to classify colors through the use of colored buttons in stringing activities, and to see the significance of the improvement. The type of research used is Classroom Action Research (CAR) with the Kemmis and Taggart model, using a qualitative approach. The subjects in this study were 14 children aged 4–5 years, 7 boys and 7 girls. Data collection techniques were through observation, interviews, and documentation. The results showed a significant increase in the ability to classify colors. In the pre-action, only 14% of children showed the ability to develop as expected. After the action was carried out in cycle I, it increased to 43%, and in cycle II it reached 100%, which is included in the category of "Developing Very Well". Thus, the colored button media in stringing activities has been proven effective in improving the ability to classify colors in early childhood and can be used as an alternative educational learning media in PAUD institutions, especially in Aisyiyah Kindergarten.Keywords: Classifying Colors, Early Childhood, Color Button Media BA II.